A comprehensive evaluation of cardiac amyloidosis epidemiology and diagnostics in French Guiana. - Baptiste Desjardins; Kénol Franck; Nathalie Deschamps; Jean-Franky Alexis; Cyrille Mathien; Franck Boteko; Grace À Dieu Yabeta; Thibaud Damy; Jocelyn Inamo; Narcisse Elenga (PLoS ONE, 2025)
Background Cardiac amyloidosis (CA) is a potentially fatal systemic disease that has received increasing attention in recent years. However, there is no data on its epidemiology in French Guiana. This study aimed to evaluate the epidemiological characteristics of cardiac amyloidosis and describe the regional diagnostic pathways in French Guiana. Methods We performed a multicenter retrospective study of Guianese patients with confirmed or suspected cardiac amyloidosis who were followed up in hospitals in French Guiana by private cardiologists. Results A total of 47 patients were included. The study population was predominantly male (n = 29, 61.7%). The mean age of the population was 72.8 years (SD = 12.2). Most patients were from the island of Cayenne (n = 34, 72.3%), had at least one cardiovascular risk factor (n = 32, 68.1%), and more than half had extracardiac amyloid involvement (n = 25, 53.2%). More than half of the patients were hospitalized at a reference center outside French Guiana (29, 61.7%), mainly at Henri Mondor Hospital (n = 20, 69%) and Martinique (n = 6, 20.7%). Bone scintigraphy was performed in 27 patients (57.5%) and hyperfixation was observed in 25 patients (93%). Anatomopathological examinations were performed in 33 patients (70.2%). Amyloid typing of the biopsied tissue revealed predominantly ATTR (n = 14, 62.6%), AL amyloidosis (n = 1, 4.5%), and AA amyloidosis (4.5%). Among the ATTR amyloidoses, we found mainly ATTRm (n = 22, 75.8%). Genetic mutation testing was performed in approximately half of the patients (n = 25, 51.1%), mostly for the VAL122ILE mutation (n = 21, 84%), and in one case for the IL107VAL mutation (4%). Of the patients with ATTR amyloidosis, 22 (75.9%) were treated with tafamidis. Of the included patients, 18 (38.3%) died. The median overall survival (OS) was 38 months. Survival analysis from the date of diagnosis showed a probability of survival at 30 days, one year, 1.5 years and 4 years of 97% (95% confidence interval [CI]: 90-100), 68% (95%CI 55-84)), 64% (95%CI 51-79)), 32% (95%CI 29-41)), respectively. Conclusion This study provides the first information on the diagnostic pathway for cardiac amyloidosis in French Guiana. The increasing proportion of undiagnosed patients has led us to create a French Guianese Amyloidosis Team to simplify the diagnostic pathway by focusing on cardiac MRI and biopsy, which can be performed locally. This is particularly important, as current and future therapeutic advances mean that more effective treatments are on the horizon.